(3YHbQjI GdJCdja GdYQHj (B:s (3YdGbGJ GdfUhU hGdGJUGd GdYdej (B/s - (3fHgGf, ceGd YQaGJs 1941-; (3GdTcYI, eUWai eMeOs 1917-2011; (3SQGL GdOjf, ESeGYjds 1944- ((3GdEScfOQjI (B- (3eUQ (B:s (3ecJHI GdEScfOQjI (B- (3EOGQI GdeTQhYGJ GdNGUI (B- (3eQcR OQGSGJ GdMVGQI GdESdGejI,s, 2015)
(3jJfGhd cJGH (S0(3YHbQjI GdJCdja GdYQHj YdGbGJ GdfUhU hGdGJUGd GdYdej(S1(3, deDdag GdOcJhQ ceGd YQaGJ fHgGf ehVhY GdJCdja cXGgQI GJUGd hGSJLGHI dMGLGJ YdejI hJYdjejI hKbGajI hGdJj ef CLdgG XgQJ BdjGJ hCUhdG aj UfYI GdJCdja hJchjf GdfUhU aj GdJCdja GdYQHj GdESdGej hCLQjJ GdOQGSI aj GdcJGH ef eONd HHdjhZQGaj heYdheGJj hGJUGdj hgj JgOa Edi eYQaI eNJda CTcGd GdYdGbGJ Hjf GdfUhU, hJUfjagG hJhVjM CHYGOgG hNUGFUgG hEHQGR Cge feGPLgG(B. (3hdaJ fHgGf aj GdebOeI fXQ GdbGQF Edi CgejI JhVjM eSCdJjf jYJHQgeG Ydi LGfH cHjQ ef GdCgejI ChdgeG Cf GdJCdja djS XGgQI bOjeI hMSHG Hd gh XGgQI eSJeQI, hGSJeQGQgG VQhQj, djS aj GdKbGaI GdYQHjI hMOgG Hd aj cd GdKbGaGJ hKGfjgeG Cf gPg GdOQGSI djSJ JCQjNG ddJCdja GdYQHj dcfgG JNVY HYV XhGgQ GdJCdja cMGdGJ ddOQGSGJ GdGSJbQGFjI ef CLd GdNQhL HJUfja dYdGbGJ GdJCdja GdfUj hJMOjO NUGFUg hJSejGJg hjbhd eDda GdcJGH Yf GdNUGFU GdGJUGdjI ddfU EPG JfGhdfG GdfU aj EWGQg GdGJUGdj cQSGdI, aEffG fbJUQ Ydi GdJYGed eY KdGKI YfGUQ QFjSjI aj GdfehPL GdGJUGd ddbQGAI hgj GdeDda, GdfU, hGdbGQF hjQcR CjVG Ydi TQM GdNUGFU GdGLJeGYjI hGdKbGajI ddfU(B.s
(3GdETQGa GdYGe (B: (3ESeGYjd SQGL GdOjf ; GdeTQa GdJfajPj (B: (3NGdO YRH ; ScQJjQ GdJMQjQ (B: (3fgi YeQ ; GdeQGLYI hGdJObjb GddZhj (B: (3SeGM QVhGf ; GdJUeje hGdENQGL Gdafj (B: (3TjQjf Hjhej(B.s
(3jTJed Ydi cTGaGJ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdCOH GdYQHjs -- (3JCdjas -- (3GdJMQjQ GdCOHjs